Tunable Electronic and Magnetic Properties of 3d Transition Metal Atom-Intercalated Transition Metal Dichalcogenides: A Density Functional Theory Study - Yujie Liu; Guang Yang; Zhiwen He; Yanbiao Wang; Xianghong Niu; Sake Wang; Yongjun Liu; Xiuyun Zhang (Inorganics)
Currently, intercalation has become an effective way to modify the fundamental properties of two-dimensional (2D) van der Waals (vdW) materials. Using density functional theory, we systematically investigated the structures and electronic and magnetic properties of bilayer transition metal dichalcogenides (TMDs) intercalated with 3d TM atoms (TM = Sc–Ni), TM@BL_MS2 (M = Mo, V). Our results demonstrate that all the studied TM@BL_MS2s are of high stability, with large binding energies and high diffusion barriers of TM atoms. Interestingly, most TM@BL_MoS2s and TM@BL_VS2s are found to be stable ferromagnets. Among them, TM@BL_MoS2s (TM = Sc, Ti, Fe, Co) are ferromagnetic metals, TM@BL_MoS2 (TM = V, Cr) and TM@BL_VS2 (TM = Sc, V) are ferromagnetic half-metals, and the remaining systems are found to be ferromagnetic semiconductors. Exceptions are found for Ni@BL_MoS2 and Cr@BL_VS2, which are nonmagnetic semiconductors and ferrimagnetic half-metals, respectively. Further investigations reveal that the electromagnetic properties of TM@BL_MoS2 are significantly influenced by the concentration of intercalated TM atoms. Our study demonstrates that TM atom intercalation is an effective approach for manipulating the electromagnetic properties of two-dimensional materials, facilitating their potential applications in spintronic devices.